Understanding Residents' Support For Intangible Cultural Heritage: A Study Of Behavioural Intention Towards Gejia Batik Preservation In Southeast Guizhou - Li, Xizhen (2025)
With accelerated industrialisation and globalisation, protecting and inheriting intangible cultural heritage has become a focal topic for scholars in recent years. In china, gejia batik is a national intangible cultural heritage with a long history and rich culture. However, its inheritance also faces challenges from social modernisation. Although a substantial amount of literature discussed the protection of intangible cultural heritage and some literature studied the inheritance and development of gejia batik, little consideration was given to residents’ support for intangible cultural heritage. Therefore, aiming to explain residents’ behavioural intention to protect gejia batik, this study establishes a new theoretical framework that connects the theory of planned behaviour and the value-attitude-behaviour model. This research adopts an explanatory sequential mixed method design to pursue the study. Firstly, the researcher collected 412 on-site survey data from four representative gejia villages to test the proposed model: fengxiang, wangba, tangdu and matang villages.